Gamification of Regional Tourism Engagement: Analysis and Design of a Web-Based Information System - Johannes Hamonangan, Siregar; Rufman Iman, Akbar; Augury, El Rayeb; Chaerul, Anwar; Suriati Khartini, Jali; Mohamad Imran, Bandan; Phei Chin, Lim; Abby Lian, Hendrick (2025)
Regional tourism often faces challenges in achieving deep and lasting tourist engagement. Gamification has emerged as a promising strategy to enhance user participation across various sectors, including tourism. This paper presents the design and development of NusaQuest, a gamified tourism learning application aimed at engaging users with Indonesian culture and destinations through quizzes, multiplayer challenges, and reward-based progression. The system integrates a structured gamification algorithm with a scalable relational database model, built using React.js and Firebase, to ensure responsive and consistent user experiences. Preliminary validation was conducted through a competition involving 15 participants, providing early evidence of user engagement and learning outcomes. A comprehensive experimental design and quantitative evaluation framework are proposed to assess usability, satisfaction, and knowledge gain through structured user studies. The findings suggest that NusaQuest holds strong potential for enhancing regional tourism engagement and promoting sustainable cultural education through digital gamification.